The Subsidy Trap: Explaining the Unsatisfactory Effectiveness of Hiring Subsidies for the Senior Unemployed - Axana Dalle; Elsy Verhofstadt; Stijn Baert (Institute of Labor Economics (IZA), 2024)
To extend the labour market participation of seniors, numerous countries provide subsidies to incentivise their recruitment or employment. Prior research demonstrates that the effectiveness of such subsidies is rather unsatisfactory, although the reasons for this inadequacy remain unclear. Therefore, we examined negative employer perceptions triggered by eligibility for such subsidies that might explain this disappointing effectiveness. To this end, we set up a vignette experiment in which 292 genuine recruiters assessed fictitious candidates on their hireability and underlying productivity estimations. These candidates differed experimentally in their eligibility for a hiring subsidy targeted at the unemployed aged 58 or over. Our results indicate that the subsidy has a negative effect on their hiring outcomes. This adverse effect is explained by negative perceptions that counteract the financial incentive. Specifically, the subsidised candidates signal lower physical and technological skills along with an augmented difficulty in hiring and labour inspection.
Keywords: J14; J38; J71; 330; hiring discrimination; senior workers; labour market programmes; hiring subsidy; signalling effect; vignettes